Experimental investigation of a novel method for heavy oil recovery using supercritical multithermal fluid flooding. (25th February 2021) - Sun, Xiaofei; Cai, Jiaming; Li, Xiaoyu; Zheng, Wei; Wang, Taichao; Zhang, Yanyu
Highlights: SCMTF flooding is a viable recovery process for deep heavy oil reservoirs. SCW has a greater role than the scN2  + scCO2 mixture in SCMTF flooding. The SCMTF at a high temperature is beneficial for the production of heavy oil. A high injection pressure is beneficial to an SCMTF flooding application. The designed setup can be used to generate SCMTF and investigate SCMTF flooding. Abstract: The objective of this study was primarily directed to the development of experimental setups to investigate the potential of supercritical multithermal fluid (SCMTF) flooding processes. Then, the recovery mechanisms of SCMTF flooding were proposed for the first time. Finally, the impact of the injection temperature, injection pressure, injection rate, and supercritical nitrogen (scN2 ) and supercritical carbon dioxide (scCO2 ) mixture amount on the SCMTF flooding performance were systematically studied in this research. The results show that SCMTF flooding is a technically and economically viable recovery process for deep heavy oil reservoirs. Supercritical water (SCW) has a greater role than the scN2  + scCO2 mixture in SCMTF flooding. The most-efficient SCMTF flooding recovered an additional 32.24% of the original oil in place (OOIP) compared to steam flooding. The injection of SCMTF at a high temperature or pressure is beneficial for the production of heavy oil. However, the high yield of coke produced at a high temperature may lead to potential formation damage. Thus, using an intermediate amount of the scN2  + scCO2 mixture in SCMTF may lead to more efficient and economical performance.